2021
DOI: 10.3390/nu13020292
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inorganic Phosphate Intake by the Measurement of the Phosphate/Urea Nitrogen Ratio in Urine

Abstract: In chronic kidney disease (CKD) patients, it would be desirable to reduce the intake of inorganic phosphate (P) rather than limit the intake of P contained in proteins. Urinary excretion of P should reflect intestinal absorption of P(inorganic plus protein-derived). The aim of the present study is to determine whether the ratio of urinary P to urinary urea nitrogen (P/UUN ratio) helps identify patients with a high intake of inorganic P.A cross-sectional study was performed in 71 patients affected by metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…In balance studies, at least two consecutive 24-hour urine collections were needed to predict Pi absorption with ≥75% reliability [ 38 ]. However, it has been suggested to normalize urinary Pi to urea nitrogen in urine, yielding a better association with dietary intake [ 39 ]. Also, random spot urine samples have been evaluated to assess the correlation with 24-hour urine Pi excretion.…”
Section: Renal Excretion and Reabsorptionmentioning
confidence: 99%
“…In balance studies, at least two consecutive 24-hour urine collections were needed to predict Pi absorption with ≥75% reliability [ 38 ]. However, it has been suggested to normalize urinary Pi to urea nitrogen in urine, yielding a better association with dietary intake [ 39 ]. Also, random spot urine samples have been evaluated to assess the correlation with 24-hour urine Pi excretion.…”
Section: Renal Excretion and Reabsorptionmentioning
confidence: 99%
“…This inaccuracy, together with hidden dietary phosphate sources, raises further concern in predicting the average intake of phosphate in CKD patients by dietary recalls and it may at least partially explain the heterogeneous results in the literature on the effects of phosphate restriction. The utility of the urinary phosphate/urea nitrogen ratio in the identification of patients with higher inorganic phosphate intake was recently demonstrated [ 176 ]. This may be used as a useful tool for monitoring hidden dietary phosphate sources in CKD patients.…”
Section: Diet and Secondary Hyperparathyroidism In Non-dialysis-dependent Ckdmentioning
confidence: 99%
“…Trautvetter et al [ 23 ], who analyzed data from 149 subjects in Germany, reported a habitual phosphate intake of more than 1300 mg per day. In contrast to phosphate in natural foods, phosphate from inorganic phosphate additives is more effectively absorbed in the intestine [ 24 ]. Although circulating Pi is tightly regulated in healthy subjects [ 25 ], our previous data show that compared to placebo, a single dose of 700 mg phosphorus administered orally as sodium dihydrogen phosphate (NaH 2 PO 4 , 3.53 g) to healthy subjects results in a significant increase in postprandial plasma Pi levels, which remain elevated over a period of 8 h post-meal (at 480 min: + 13%) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%